The Forming Factors of Accounting Information System Performance in the Framework of Involvement and Capability of Accounting Information System Users - Hani Fitria Rahmani (Enrichment : Journal of Management, 2021)
The problem of this study is the lack of involvement and the ability of users to have an impact on reporting existing accounting information systems. Reporting the accounting information system is one form of performance that needs to be achieved by the existing accounting information system. The purpose of this study is to determine the factors that influence the performance of accounting information systems, namely the involvement and abilities of users of accounting information systems. This study took a sample of all BOS Fund Subrayon Junior High School District Education Agency Operators. Kab. West Bandung with saturated sample technique. Data collection is done by survey method. The analysis technique in this study uses multiple linear regression analysis. The results of the analysis show that the factors that influence the performance of the accounting information system are user involvement, user abilities which results that user involvement and user abilities have a positive and significant effect on the performance of accounting information systems. Contributions from the results of this study provide advice to the relevant agencies to make improvements to the variables examined in this study so that the performance of the information system is running optimally.